RELACIONES DE PODER Y GÉNERO EN PROYECTOS DE AGRICULTURA URBANA EN LIMA SUR: UN ANÁLISIS CRÍTICO DE LA PARTICIPACIÓN COMUNITARIA - Serrano Ayasta, Luis Enrique (2025)
This article presents the findings of a doctoral research study focused on power relations within urban agriculture (UA) projects in three low-income neighborhoods in South Lima. The research emerges within a social context marked by deep socioeconomic inequalities and a history of internal migration. Although these projects are framed with objectives of food security, social inclusion, and empowerment, the findings reveal that they often mask asymmetric power relations that impact the residents of these areas, especially the gardeners, who are mostly women. Using a methodological approach that combines critical discourse analysis and deep hermeneutics, the study explores power dynamics among promoting organizations, community leaders, and participants. It is identified that, far from empowering the gardeners, these projects reinforce preexisting inequalities, perpetuating gender hierarchies and structures of subordination that limit their participation and agency. The interactions among the various actors reflect a paternalism that disregards the lived realities of the gardeners, who, by accepting imposed directives, reproduce discourses that do not reflect their everyday experiences. The gardeners’ self-devaluation and deference towards promoters demonstrate how structural prejudices and inequalities shape these dynamics. In conclusion, this study highlights the need for a critical review of UA discourses to achieve genuine empowerment and social transformation within South Lima communities.